A BRIEF REVIEW OF THE HEALTH AND NUTRITIONAL STATUS OF THE RURAL WOMEN OF UTTARAKHAND (International Journal of Food and Nutritional Sciences, 2023)
Nutritional status is the health of an individual based on the nutrient’s intake. The nutrients we receive via food we eat not only helps in our survival and day-to-day activities but also influences our health. Good nutrition is necessary to maintain good health. Nutrition plays a significant role in our growth and development. Good nutrition ensures a good and healthy life and also helps in fighting against many diseases. Women, especially rural women have always been on the poorer side of health and nutrition and there are various factors responsible for it, poor dietary intake, lifestyle and lack of knowledge are among these factors behind the poor nutrition status of rural women. There is also a lack of knowledge on health and nutrition. Furthermore, poor access to information, societal beliefs and myths, socio-economic factors also contribute to the poor nutrition status among the rural women. There are many studies that have reported the poor nutritional status of the rural women along with further suggestion to improve their nutritional status. Therefore, this is a brief review intended to assess the nutritional status of the rural women of state of Uttarakhand. The review also aims to suggest ways to improve the nutritional status of the rural women. For this purpose, 8 studies conducted between 2010 and 2020 among the rural women of Uttarakhand aged between 15-60 years have been taken under review.